2008
DOI: 10.1098/rsif.2008.0067.focus
|View full text |Cite
|
Sign up to set email alerts
|

Combining experiments and modelling to understand size regulation inDictyostelium discoideum

Abstract: Little is known about how the sizes of specific organs and tissues are regulated. To try to understand these mechanisms, we have been using a combination of modelling and experiments to study the simple system Dictyostelium discoideum, which forms approximately 20 000 cell groups. We found that cells secrete a factor, and as the number of cells increases, the concentration of the factor increases. Diffusion calculations indicated that this lets cells sense the local cell density. Computer simulations predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 76 publications
(115 reference statements)
1
22
0
Order By: Relevance
“…During early development, cells release a complex of at least 5 proteins called counting factor (CF) that causes aggregation streams to break up and form multiple independent aggregates of about 2 × 10 4 cells (Tang et al, 2002). High levels of CF decrease cell-cell adhesion and increase random motility such that aggregation streams break up and form small aggregates as predicted by a computer simulation (Jang and Gomer, 2008). CF also decreases the amplitude of cAMP-stimulated cAMP pulses which could limit spread of the signal.…”
Section: Early Developmental Signalsmentioning
confidence: 88%
“…During early development, cells release a complex of at least 5 proteins called counting factor (CF) that causes aggregation streams to break up and form multiple independent aggregates of about 2 × 10 4 cells (Tang et al, 2002). High levels of CF decrease cell-cell adhesion and increase random motility such that aggregation streams break up and form small aggregates as predicted by a computer simulation (Jang and Gomer, 2008). CF also decreases the amplitude of cAMP-stimulated cAMP pulses which could limit spread of the signal.…”
Section: Early Developmental Signalsmentioning
confidence: 88%
“…In addition to the influence of the cAMP relay, the integrity of the aggregates is governed by two other major factors: (a) chemotaxis towards cAMP and (b) cell–cell adhesion (Gomer et al ., 2011; Jang and Gomer, 2008; Pálsson et al ., 1997). To measure cell movement in response to a cAMP gradient, we performed an under-agarose cAMP chemotaxis assay (Woznica and Knecht, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of cells to form stable, appropriately sized aggregates depends upon cAMP relay, chemotaxis, cytoskeletal dynamics and cell–cell adhesion (McMains et al, 2008). It is reported that when the equilibrium between chemotaxis and cell–cell adhesion factors is disturbed, streams break and reorganize themselves to form individual mounds (Jang and Gomer, 2008). We see that pkcA − cells have enhanced chemotactic speed and decreased cell–cell adhesion, most likely due to increased F-actin polymerization and reduced expression of adhesion molecules, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major emphasis of the workshop was modelling of signalling networks, for example, pheromone signalling in yeast (Behar et al 2007), bacterial chemotaxis (Keymer et al 2006), regulatory circuits in the AIDS virus (Weinberger & Shenk 2007;Weinberger et al 2008) and osmo-adaptation in yeast . In this special issue, the relevant contributions are by Csikasz-Nagy & Soyer (2008) on 'adaptation' in a simple biochemical network and by Jang & Gomer (2008) on size regulation in Dictyostelium.…”
Section: Modern Developmentsmentioning
confidence: 99%